Frequency and prognostic value of circulating tumor cells in cancer of unknown primary - Pouyiourou, Maria; Bochtler, Tilmann; Coith, Cornelia; Wikman, Harriet; Kraft, Bianca; Hielscher, Thomas; Stenzinger, Albrecht; Riethdorf, Sabine; Pantel, Klaus; Krämer, Alwin (Clinical chemistry, 2024)
Cancer of unknown primary (CUP) is defined as a primary metastatic malignancy, in which the primary tumor remains elusive in spite of a comprehensive diagnostic workup. The frequency and prognostic value of circulating tumor cells (CTCs), which are considered to be the source of metastasis, has not yet been systematically evaluated in CUP.A total of 110 patients with a confirmed diagnosis of CUP according to the European Society for Medical Oncology (ESMO) guidelines, who presented to our clinic between July 2021 and May 2023, provided blood samples for CTC quantification using CellSearch methodology. CTC counts were correlated with demographic, clinical, and molecular data generated by comprehensive genomic profiling of tumor tissue.CTCs were detected in 26% of all patients at initial presentation to our department. The highest CTC frequency was observed among patients with unfavorable CUP (35.5%), while patients with single-site/oligometastatic CUP harbored the lowest CTC frequency (11.4%). No statistically significant association between CTC positivity and the number of affected organs (P = 0.478) or disease burden (P = 0.120) was found. High CTC levels (≥5 CTCs/7.5 mL; 12/95 analyzed patients) predicted for adverse overall survival compared to negative or low CTC counts (6-months overall survival rate 90% vs 32%, log-rank P < 0.001; HR 5.43; 95% CI 2.23-13.2). CTC dynamics were also prognostic for overall survival by landmark analysis (log-rank P < 0.001, HR 10.2, 95% CI 1.95-52.9).CTC frequency is a strong, independent predictor of survival in patients with CUP. CTC quantification provides a useful prognostic tool in the management of these patients.
Veröffentlicht: 4. Januar 2024
Gesehen am 10.06.2024